RECOGNITION OF COMMUNAL LAND RIGHTS IN SUSTAINABLE DEVELOPMENT AND ENVIRONMENTAL PROTECTION - Gloria Gita Putri Ginting; Henry Aspan; Mhd. Azhali Siregar; Ayu Kurnia Sari (PT. Radja Intercontinental Publishing, 2026)
This research aims to analyze the recognition of communal land rights of indigenous communities within the framework of sustainable development and environmental protection. Customary land is not merely an economic asset, but rather the foundation of the cultural identity, social structure, and survival of indigenous communities. Although the 1945 Constitution, through Article 18B paragraph (2) of the 1945 Constitution, mandates the recognition and respect of indigenous communities and their traditional rights, its implementation still faces various challenges. The research method used is a juridical-normative approach, supported by case study analysis from various regions in Indonesia, including West Sumatra, Papua, and Rempang. Data were collected through a review of relevant laws and regulations, policy documents, and various previous studies. The results show that the recognition of communal land rights is closely linked to environmental sustainability. Indigenous communities play a crucial role in maintaining ecosystem sustainability through local wisdom practices passed down through generations. However, a development paradigm that still views nature as an object of extraction often ignores these communal rights. The government has demonstrated its commitment by issuing 41 Management Rights Certificates for customary land in seven provinces. However, this policy also has the potential to create conflict if it does not involve communities meaningfully. This study concludes that recognizing communal land rights must be the foundation of inclusive, sustainable development, using local wisdom as a guide and ensuring the active participation of indigenous communities in all decisions concerning their land and territories.